Upper extremity motion and sprint running: a farewell to arms? - Brooks, L.; Weyand, P. G.; Clark, K. P. (ISBS Proceedings Archive (Michigan), 2020)
Despite a lack of prior research on the topic, the sport coaching community has popularized the use of arm drills for athletes with the intent to enhance sprinting performance. The purpose of this study was to identify the effect of self-restricted arm motion on sprint running velocity. Track & field athletes and team sport athletes (n=15) completed 12 30-meter sprints (six with normal arm motion, six with restricted arm motion) while radar data was collected to quantify running velocity. Using a mono-exponential function, velocity profiles were created for each trial which produced four outcome variables: vmax, amax, t, and 30-meter sprint time. Differences in group means for all four outcome variables were not substantial between the two experimental conditions. It was concluded that the use of arm motion during maximal effort sprinting does not play a major role in running velocity enhancement.